Assay for heavy metals. - Abd. Shukor, Mohd. Yunus; Baharom, Nor Azlan; Syed, Moh Arif; Hamid, Muhajir; Abdullah, Puad (2010)

(untitled)
A method and kit for assaying heavy metals for a sample solution suspected of containing heavy metals is disclosed. The method comprises the steps of incubating the sample with enzyme pap.